Compact H-Plane CLAF-SIW Horn Antenna With Phase Front Correction - Andres Biedma-Perez; Cleofas Segura-Gomez; Angel Palomares-Caballero; Pablo Padilla (IEEE Access)
This work presents an H-plane contactless air-filled substrate-integrated waveguide (CLAF-SIW) horn antenna, whose directivity is enhanced by incorporating a metalens along the horn flaring. By tuning the distribution of the unit cells of the metalens, it is possible to reduce phase errors at the aperture, a common issue in horn antennas. The unit cell of the metalens is designed by using a metallic patch on a substrate-integrated hole. By varying the size of the metal patches, different refraction indices can be tuned, resulting in a wideband performance. An analysis of the distribution of these unit cells along the horn antenna is conducted to achieve the desired equivalent effective refraction index through the metalens. The directivity achieved is comparable to that of a horn antenna with optimal dimensions, but with a 41% reduction in length. The measured results demonstrate an impedance bandwidth below −10 dB from 32.8 to 50 GHz, with a realized gain above 9.3 dBi.